PENGEMBANGAN BAHAN AJAR SENI RUPA MEKARSI (MELAYU, KARO DAN SIMALUNGUN) BERBASIS CASE METHODE SEBAGAI PENGUATAN IMPLEMENTASI MERDEKA BELAJAR - Afriadi, Putra; Betty Simanjuntak, Eva; Silalahi, Natalia (Universitas Negeri Medan, 2024)
Developing effective and interesting learning media is very important in the educational process, especially at the elementary school level. This article discusses the development of teaching materials for learning money arts specifically for elementary school children in the Malay, Karo and Simalungun families. The research method used is Research and Development (R&D) based on the model proposed by Borg and Gall. Research steps include initial research and information gathering, planning, product design development, initial field trials, product revisions, main field trials, final product revisions, and dissemination. The results of the research show that the use of developing fine arts teaching materials in learning is effective in increasing students' interest, understanding and artistic skills in regional fine arts. Students are more enthusiastic and creative in taking art lessons using learning media. Comparison of conventional methods. Teachers also find it easy to convey art material in a more interactive and interesting way. This learning media helps students learn more practically and contextually, which in turn increases their understanding of the material being taught. Thus, developing fine arts learning media can be an innovative solution to improve the quality of fine arts learning in elementary schools. It is hoped that this article can be a reference for educators in utilizing regional culture to create a more enjoyable and meaningful learning experience for students.